Predicting Retirement Upon Eligibility: An Embeddedness Perspective. Issue 1 (29th October 2013) - Bamberger, Peter A.; Bacharach, Samuel B.
Abstract Concern over the impact of baby‐boomers' retirement on needed skills and proprietary knowledge has stimulated an interest in identifying workplace factors associated with retirement upon eligibility. Drawing from embeddedness theory, the authors identify work‐based antecedents potentially underlying a related, but distinct, form of withdrawal—retirement upon eligibility. The authors generate and test hypotheses regarding the impact of fit‐, sacrifice‐, and links‐related antecedents using a prospective study design and a national probability sample of some 500 older individuals who, at the time of the initial interview, were within months of becoming—for the first time—eligible to receive such benefits. The findings indicate that, beyond the effects of person‐based antecedents (e.g., age, health, assets, expected retirement income), a combination of fit‐ (i.e., job challenge), sacrifice‐ (i.e., perceived organizational support), and links‐related factors (i.e., stability of close workplace peer relations) have a substantial influence on the decision to retire upon eligibility. © 2013 Wiley Periodicals, Inc.